Thermodynamic analysis of a renewable energy-water-food nexus: A trade-off analysis of integrated desalination, gasification and food systems - Jamileh Fouladi (16932549) (2022)
Today, the global demand for food, energy, and water resources continues to increase. As such, this study proposes a solar energy-based system integrated with a utility unit to produce fresh water from seawater desalination, power, ammonia/urea, and syngas from biomass gasification. The objective is to study the dependence of the energy-water-food nexus performance over the solar capacity and to capture the trade-offs among different resources. The key components of the integrated system include solar thermal collectors, Rankine cycle, reverse osmosis desalination unit, food/agriculture unit, biomass gasification process, ammonia and urea production units. Furthermore, the beneficial uses of reverse osmosis brines streams in agriculture sector are considered. The syngas produced from gasification process is used for ammonia/urea production and a Rankine cycle for electricity production. A comprehensive thermodynamic model and energy and exergy balances are used to evaluate the performance of the proposed system. Moreover, the effects of different parameters on the system efficiencies are investigated. The overall energy and exergy efficiencies of the proposed system are 45.77% and 18.92%, respectively. The outcomes demonstrate that by using the solar collectors, the system is able to produce almost 78 MW electricity, 28 kg/s freshwater, and 7 kg/s ammonia/urea fertilizer for agricultural purposes. Other Information Published in: Case Studies in Thermal Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.csite.2022.102024